(untitled) (Chemical Engineering Research Bulletin, 2013)
SiO2/Silicalite-1 core-shell material has been demonstrated as potential shape selective adsorbent in gas phase separation of p-xylene from a mixture of p/o-xylene isomers. The core-shell composite comprised of large silica core and thin polycrystalline silicalite-1 shell which was synthesized via a self-assembly of silicalite-1 nanocrystals on core silica surface followed by a secondary seeded growth method. The core materials, SiO2 used in this study has mesoporosity with an average pore diameter of 60Å and hence offers no shape selectivity for xylene isomers. However, the shell, silicalite-1 contains rigid pore structures and preferentially adsorbs p-xylene from their isomers mixtures. A series of adsorption fixed bed breakthrough adsorption/desorption experiment was performed to obtain the equilibrium isotherms and adsorption isotherm parameters of xylene isomers. The equilibrium isotherms of xylene isomers follow the Langmuirs model. A chromatographic adsorption model has been used to describe the fixed-bed breakthrough profiles of xylene isomers. The model has successfully predicted the responses of the binary mixtures of p/o-xylene isomers. The SiO2/silicalite-1 core-shell adsorbents have shown para-selectivity as high as 15. DOI: http://dx.doi.org/10.3329/cerb.v16i1.17470 Chemical Engineering Research Bulletin 16(2013) 1-15